Perkembangan Bahasa Anak Usia 12 Hingga 24 Bulan di Semarang - Marini, Marini; Khasanah, Khasanah (Journal of Studies in Early Childhood Education (J-SECE), 2018)
Abstract The  problem  of this research is : How is the language development of children age 12 to 24 months in Semarang ?. The purpose of this study is to describe widely and deeply about language development the children age 12 to 24 in Semarang. The method used in this research is qualitative method. Data collection is done by observation, interviews, and questionnaire. Data analysis techniques using Miles Hubermenâs model. Checking the validity of the data using triangulation data. The results showed that the development of language of children aged 12 to 24 months in Semarang in expressive is: can produce sound almost perfect in several words; Some of the letters of the words missing from the pronunciation; The missing letters are usually consonants; Havent been able to pronounce the letter s and r; In General, most people are able to understand the speech of the children is an adult who is close to the child; There is a word that can be spelled perfectly by the child. The words are by and large is the words that are simple and close to the childrens daily lives. As for the generally receptive: children can follow and obey what is spoken by adults; The children seem to understand when the adults were talking about them; and children  can understand  to the words that they  heard more than that they can speak.   Keywords: Language, children, expressive, receptive, word.